The methodical approaches of improvement of control of quality of making of products on food enterprises - Ткаченко, Тарас Ігорович (Technology audit and production reserves, 2012)
In the articles described results of methodical approaches of improvement of control of quality of making of products are for food enterprises on the basis of development and introduction of the system of management of quality (SMYA). Conceptual positions of creation of the computer-integrated systems of management of quality are offered on enterprises on the basis of introduction of requirements of standards of ISO 14001, OHSAS 18001 and SA 8000